Vaginal estrogen use and effects on quality of life and urogenital morbidity in postmenopausal women after publication of the Women's Health Initiative in New York City. Issue 1 (January 2016) - Setty, Prathima; Redekal, Laura; Warren, Michelle P.
Abstract: Objective: In the years after the 2002 publication of results from the Women's Health Initiative study, there has been a reluctance to prescribe hormone therapy to symptomatic postmenopausal women and confusion over its duration and method of prescription. The main concerns are the risks of cardiovascular events and breast cancer. However, local vaginal estrogen (VE) may provide benefits without systemic effects. Methods: This study investigates the use and effects of VE on quality of life and urogenital morbidity among women who stopped hormone therapy after the Women's Health Initiative and compares them with women who continued hormone therapy. Three groups were compared: group 1, women who have remained on HT/ET; group 2, women who have resumed HT/ET after stopping for at least 6 months, and group 3, women who have stopped HT/ET and have not resumed. Results: Overall, ever use and present use of VE were most prevalent in women who reported dyspareunia (ever, P  = 0.003; present, P  = 0.005) and vaginal dryness (ever, P  = 0.001; present, P  = 0.004). VE use was significantly more probable for women in group 3 than for women in the other groups (group 3 [3.5%] vs group 1 [17.7%] and group 2 [16.7%]; P  = 0.002). Women in group 3 who used VE reported significantly higher sexual quality of life (using the sexual domain of the Utian Quality of Life Scale) compared with women in group 3 who did not use VE ( P  = 0.007). There was no difference in the incidence of urinary tract infections between the three groups (group 1, 22.9%; group 2, 26.3%; group 3, 25.5%). The percentage of women who were either married or living in a marriage-like relationship did not differ between the three groups (group 1, 68.4%; group 2, 78.6%; group 3, 78.8%). Conclusions: Women who report dyspareunia and vaginal dryness are more likely to use VE. Women who do not use systemic therapy but use VE score significantly higher on the sexual quality-of-life scale than women not using VE.